Addresses on the Revised Version of Holy Scripture - Ellicott, C. J. (Charles John), 1819-1905 (Salt Lake City, UT : Project Gutenberg, 2008)
"Addresses on the Revised Version of Holy Scripture" by C. J. Ellicott is a theological work written in the early 20th century." This publication outlines a series of addresses concerning the Revised Version of the Holy Scriptures, focusing on the historical context of the revision process and advocating for its usage in church services. Ellicott, as a bishop and a prominent church figure, aims to inform the clergy and laity on the importance of this updated scripture. "The opening of this work introduces the background and rationale behind the addresses delivered at the Archdeaconry of Cirencester's visitation." Ellicott discusses the historical timeline of the Revised Version, noting that it has been in circulation for over a decade and was composed following the need for more accurate interpretations of the Holy Scriptures. He emphasizes the necessity of genuinely understanding the development of the Revised Version and suggests that it is high time for its more widespread adoption in public worship settings, given its critical reception and the advancements in scriptural scholarship over the years. (This is an automatically generated summary.)
Release date is 2008-05-09
Transcribed from the 1901 Society for Promoting Christian Knowledge edition by David Price
Keywords: Bible. English -- Versions -- Revised